Pengaruh Kualitas Pelayanan Dan Customer Relationship Management Terhadap Loyalitas Nasabah Pada Bank BRI - Erline, Erline; Saputra, Boby (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2020)
This study aims to determine whether service quality affects customer loyalty at BRI Bank Muara Teweh Branch. Does Customer Relationship Management affect customer loyalty at BRI Bank Muara Teweh Branch Office This research method uses the data analysis technique used, namely the analysis of Structural Equation Modeling from the IBM SPSS Statistics Amos version 20 program AMOS (Analysis of Moment Structures) analysis program Structural Equation Modeling (SEM) a covariance-based The results of this test show significant results with a CR value of 3.848> 1.96 and the p number is 0.000, this number is far below 0.05 so that H0 is rejected and H1 is accepted, which means that there is an influence between service quality on customer loyalty This test shows significant results with a CR value of 2.322> 1.96 and the p number is 0.006, this figure is far below 0.05 so that H0 is rejected and H1 is accepted, which means that there is an influence between customer relationship management on customer loyalty The results of the study concluded that service quality variables have a significant and positive influence on customer loyalty variables customer relationship management have a significant and positive influence on customer loyalty. For further researchers, it is suggested that the Muara Teweh branch of BRI bank improve the quality of their services to increase customer loyalty.